Heat Transportation of Ferrofluid in a Micro Annulus - Muhammad Sajid; Ahmad, Bilal; Muhammad Tariq Ali; Jihad Ahmed Younis (Scientific Inquiry and Review, 2021)
This article investigated the effect of magnetic field on heat-absorbent ferrofluid in a vertical loop consisting of a pair of concentric cylinders with surface sliding and temperature jumping. For this puprose, the control equation was converted into the dimensional form using non-dimensional quantities and parameters. The system of equations was solved analytically using an integration technique. Subsequently, the solution was obtained in the form of first and second type of Bessel functions. The results are presented graphically and show that velocity increases with the increase in the nanoparticle size. Resultantly, the rate of heat transfer of the fluid in the inner cylinder reduces.